2020
DOI: 10.1186/s12995-020-0253-x
|View full text |Cite
|
Sign up to set email alerts
|

Are social conflicts at work associated with depressive symptomatology? Results from the population-based LIFE-Adult-Study

Abstract: Background: Psychosocial stressors in the workplace can be detrimental to mental health. Conflicts at work, e.g. aggression, hostility or threats from coworkers, supervisors or customers, can be considered a psychosocial stressor, possibly increasing risk for depressive symptoms. Existing studies, however, differ in the assessment of social conflicts, i.e. as individual-or job-level characteristics. Here, we investigated the association between conflicts at work assessed as objective job characteristics, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 77 publications
0
20
1
1
Order By: Relevance
“…Interestingly, no gender differences were found in general health or social support. These results contrast with previous studies, which reported gender differences among health care professionals ( Leiter and Maslach, 2009 ; Sweile, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, no gender differences were found in general health or social support. These results contrast with previous studies, which reported gender differences among health care professionals ( Leiter and Maslach, 2009 ; Sweile, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Different components (deliberative, affective, or experiential [ 20 ]), and many factors are involved in the formation of risk perceptions, including literacy and numeracy levels [ 21 ], dispositional situations [ 22 ], personal experiences, information availability and presentation [ 23 ], and physical and psychological well-being of the exposed individual [ 24 ]. Health risk perception of chemical exposure has been assessed in numerous settings and targeted populations (e.g., drinking water quality [ 25 ], chemical household products [ 24 , 26 ], food additives and contaminants [ 27 ], research laboratory workers [ 28 ], or recreational beach use by children [ 29 ]), as a starting point, to build-up effective risk communication strategies and public health interventions, which ultimately may lead to risk perception and health behaviour changes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ], dass körperliche Beanspruchungen des Herz-Kreislauf-Systems im Unterrichtsgeschehen in ihren Höchstbelastungen durchaus submaximale bis maximale Intensitäten erreichen können. Andererseits fallen durchschnittliche Herz-Kreislauf-Belastungen im Unterrichtsverlauf häufig gering bis moderat aus [ 20 ], und mit der Berufsausübung kann nicht automatisch eine höhere Fitness verbunden werden [ 12 ]. Eine ähnliche Beobachtung im Hinblick auf die Wirkung berufsbezogener körperlicher Aktivität lässt sich in der Studie von Bogaert et al.…”
Section: Körperliche Arbeit Mit Ambivalenter Wirkungunclassified